Diversificação geográfica e desempenho financeiro e social em cooperativas de crédito brasileiras - Laís Karlina Vieira (2023)
Geographical diversification is an alternative to be used by organizations seeking growth and better performance, so studying this phenomenon in credit unions is an opportunity to explore its relationships. In this context, this research aimed to evaluate the relationship between geographical diversification and the financial and social performance of Brazilian credit unions. It studied 644 unique credit unions from December 2016 to June 2022. The methods used were Principal Component Analysis (PCA) and the System Generalized Method of Moments (System GMM), which resulted in the operationalization of 44 different models. In this research, the PCA was first used to disaggregate the performance of the cooperatives into different components, in which four components were identified: Financial Performance Index (Comp1), Breadth of Reach Index (Comp2), Financial and Social Growth Index (Comp3), and Depth of Reach Index (Comp4). The components covered the financial and social dimensions of credit union performance, with Comp1 being a financial performance indicator, Comp2 and Comp4 being social performance indicators, while Comp3 was a financial and social growth indicator. Subsequently, the results of the models indicated that geographical diversification affected the performance of credit unions, however the way in which this relationship develops depends on which aspect of the cooperatives' performance is being assessed. In this sense, the results of the study showed that: (i) higher levels of geographic diversification were associated with lower financial performance (Comp1), and there was a minimum point at which geographic diversification would positively affect this performance; in addition, increasing the diversification of financial products and services also reduced financial performance, but working with both forms of diversification provided better financial results; (ii) Geographical diversification has been shown to be beneficial for social performance as measured by Breadth of Reach Index, but there is a limit to this benefit, suggesting that too much geographical diversification, beyond an optimum point, can be detrimental to social performance; (iii) the increase in geographical diversification promoted the financial and social growth of credit unions, as did the increase in the diversification of products and services; however, the interaction between the two forms of diversification and the increase in the distance between the states in which credit unions have branches proved to be detrimental to this growth; (iv) finally, it should be noted that the main variables of interest studied did not prove to be significant for the social performance measured by the Depth of Reach Index. Thus, this research stands out for being one of the first studies on geographic diversification and performance in credit unions, for innovating by demonstrating the relationship between geographic diversification and both financial and social performance, as well as for testing geographic diversification in performance indices obtained through PCA. It is believed that its results may be relevant for regulators of the cooperative system and for credit union managers, by demonstrating that geographic diversification can present different relationships depending on which aspect of performance is being analyzed, as well as by emphasizing the need to seek geographic diversification that provides a balance between the dimensions of cooperative performance.